An exploratory study of maternal predictors affecting the health status of married women’s children in East Asia - Jung, Minsoo (Korean Journal of Health Education and Promotion, 2021)
Objectives: Although maternal characteristics are important predictors with regard to population-based health promotion, they have not been fully identified in many countries and cultures. This study explores the effects of maternal capacity and health communication behaviors on children’s health statuses in Korea, China and Japan. Methods: The dataset came from a survey of respondents drawn from a nationally representative online sample of women in East Asia. We conducted computer-assisted web interviews with married women in their 20s-40s holding South Korean, Chinese, or Japanese nationality (n=1580). We designed a cross-sectional study to examine the effects of certain maternal capabilities, in this case self-efficacy, empowerment, and e-health literacy, on the low health status of the participants’ children with health-information-seeking behavior (HISB) as a potential moderator. Results: The results showed that the likelihood of belonging to the low health status group among children was a mother with low self-efficacy, a mother who was poorly empowered, and a mother who had poor e-health literacy. However, a positive association was found between active HISB by the mother and low health status of the child. Conclusion: Factors constituting maternity capacity differentially influenced children’s health status according to the social context of East Asian countries. KCI Citation Count: 0